2014
DOI: 10.1002/ange.201408810
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Fluorescent Probe to Amyloid‐β to Reveal Kinetic Insights into Its Interactions with Copper(II)

Abstract: The kinetics of the interactions between amyloid‐β (Aβ) and metal ions are crucial to understanding the physiological and pathological roles of Aβ in the normal brain and in Alzheimer’s disease. Using the quenching of a fluorescent probe by Cu2+, the mechanism of Aβ/Cu2+ interactions in physiologically relevant conditions has been elucidated. Cu2+ binds to Aβ at a near diffusion‐limited rate, initially forming component I. The switching between component I and II occurs on the second timescale, with a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Here we report the effects of the H50Q mutation and N‐terminal acetylation on Cu 2+ binding to αSyn from kinetic perspective. Highly sensitive fluorescent probe was used to detect fast reaction kinetics as reported previously [29–31] . We have found that His50 in αSyn is not involved in high‐affinity Cu 2+ binding, whereas N‐terminal acetylation reduces the Cu 2+ binding affinity of αSyn by approximately four orders of magnitude.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Here we report the effects of the H50Q mutation and N‐terminal acetylation on Cu 2+ binding to αSyn from kinetic perspective. Highly sensitive fluorescent probe was used to detect fast reaction kinetics as reported previously [29–31] . We have found that His50 in αSyn is not involved in high‐affinity Cu 2+ binding, whereas N‐terminal acetylation reduces the Cu 2+ binding affinity of αSyn by approximately four orders of magnitude.…”
Section: Introductionmentioning
confidence: 80%
“…Kinetic techniques have been employed recently in several studies to give insights into IDP‐Cu 2+ interactions [28–31] . In brain, the existence of labile Cu 2+ released in synaptic cleft during neuronal excitation is transient.…”
Section: Introductionmentioning
confidence: 99%
“…4 Aβ encounters metal ions during synaptic transmission and it has been proved as a crucial step in the amyloid cascade. 5 It has been found that under physiological conditions, Zn 2+ not only rapidly induced Aβ oligomerization but also significantly enhanced the toxicity of Aβ species. 6,7 Although many studies have investigated the involvement of Zn 2+ in Aβ aggregation, the molecular mechanisms of Zn 2+ −Aβ interactions are still not clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…HDPs often cause the death of microorganisms by interacting with the lipid bilayer and then determining membrane disruption in a specific, but not receptor-mediated, process [ 15 , 66 ]; several models have been proposed to describe this process of membrane permeabilization. In recent years, it has been also demonstrated that several HDPs have the ability to form β-sheet-rich amyloid-like fibrillar structures, what has led to postulate the existence of two seemingly unrelated classes of polypeptides, HDPs and fibril-forming (amyloidogenic) antimicrobial peptides, that share common mechanisms of cytotoxicity based on membrane disruption [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The deposits known as amyloids exhibit a characteristic cross-β structure that allows them to exert toxic effects by forming ion channels in bacterial cell membranes, thus causing membrane depolarization, energy drainage, and in some cases apoptosis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obtained results did not highlight significant differences, since, in the case of both ApoB-derived peptides, a surface interaction with lipid head groups coupled with a lipid segregation process has been demonstrated, while both peptides are not able to destabilize the hydrophobic core of the bilayer ( Figure 3 ). It has been reported that the formation of lipid domains in membranes can have a deep impact on the biological activity of the cells [ 74 ], such as an alteration of the diffusion rates of lipids and membrane proteins and an interference with membrane physiological curvature, with a consequent negative impact on key processes, such as cell division [ 14 ]. In the present manuscript, circular dichroism analyses reveal conformation shifts from a random-coil structure to a structural ensemble comprising significant β-sheet conformation, in the case of both peptides upon incubation with LPS or LTA ( Figure 4 c,d, Tables S3 and S4 ).…”
Section: Discussionmentioning
confidence: 99%